PROSPECTS FOR THE DEVELOPMENT OF FREEDOM OF SPEECH IN THE DIGITAL SPACE - Oripov Hasan Abdivakhobovich (American Journals Publishing, 2022)
The article examines the importance of digital technologies in the development of freedom of speech, the role of the digital revolution in the cultural life of a democratic society, and also analyzes the importance of freedom of speech in society.
Keywords: Freedom of speech, democracy, society, digital space, technology, culture.